2022
DOI: 10.3390/biology11060920
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Features and Microanatomy of the Lingual Filiform Papillae in the Wistar Rat

Abstract: The mammalian tongue plays a fundamental role in various physiological and behavioral activities. Significant morphological variations have been recorded in the tongue of several species. This study aims to obtain detailed histological and morphometric information about the filiform papillae on the surface of rat tongue. The tongues of five 10-month-old Wistar rats were utilized, which were later examined with a stereo-microscope. Fragments from the three regions of the tongue were collected for histological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The tips of these papillae were generally oriented in the caudal direction. The distribution of filiform papillae on the tongue in squirrels was similar to the distribution of filiform papillae found in the tongues of Wistar rat (10), guinea pig (12), Jentink's flying squirrel (18) and agouti (22). A weak keratinized layer was present on the epithelial surface of the filiform papillae on the tongue in squirrels, similar to reports of the filiform papillae in rats ( 8) and Jentink's flying squirrels (18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The tips of these papillae were generally oriented in the caudal direction. The distribution of filiform papillae on the tongue in squirrels was similar to the distribution of filiform papillae found in the tongues of Wistar rat (10), guinea pig (12), Jentink's flying squirrel (18) and agouti (22). A weak keratinized layer was present on the epithelial surface of the filiform papillae on the tongue in squirrels, similar to reports of the filiform papillae in rats ( 8) and Jentink's flying squirrels (18).…”
Section: Discussionsupporting
confidence: 83%
“…Macroscopic and light microscopic properties of both mechanical and gustatory papillae found on tongues of many species belonging to the rodent order were investigated. Accordingly, the macroscopic, light microscopic and scanning electron microscopic structures of the papillae of the mouse (4-7), rat (8)(9)(10)(11), guinea pig (12,13), porcupine (14,15), hamster (16), Japanese lesser flying squirrel (17), Jentink's flying squirrel (18), greater cane rat (19), American beaver (20), capybara (21), agouti (22), hazel dormouse (23), large bamboo rat (24) and paca (25) were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Both microscopic and ultrastructural analyses revealed that the lingual papillae could be differentiated according to their function. The mechanical and the gustatory represent the main forms and similar arrangement was recognized in several mammalian species such as the European hedgehog (Akbari et al, 2018), Horsfield's tree shrew (Gartiwa et al, 2021), the gray mongoose (Mahmood et al, 2022), the Egyptian long‐eared hedgehog and the Nile grass rat (Massoud & Abumandour, 2019), Wistar rat (Huțanu et al, 2022), common opossum (Okada & Schraufnagel, 2005), the Egyptian fruit bat and the Egyptian tomb bat (El‐Mansi et al, 2019), lowland tapir (Goździewska‐Harłajczuk et al, 2020), African pygmy hedgehog (Cizek et al, 2022), rakali and the greater stick‐nest rat (Humphries et al, 2023). Fork filiform papillae carrying two or three spines were described previously in other hedgehogs, including the long‐eared hedgehog (Massoud & Abumandour, 2019) and Brandt's hedgehog (Goodarzi & Azarhoosh, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…The macroscopic observations showed that there was no lingual prominence detected on the tongue dorsum. The emergence of this part in the tongue dorsum was detected in several species, including Sulawesi bear (Goździewska‐Harłajczuk et al, 2022), koala (Kobayashi et al, 2003), Egyptian water buffalo (Farrag et al, 2022), lowland tapir (Goździewska‐Harłajczuk et al, 2020), barking deer (Adnyane et al, 2010), Wistar rat (Huțanu et al, 2022), and Nile grass rat (Massoud & Abumandour, 2019). It appears that the existence of lingual prominence is closely linked to herbivorous feeding habits to grind grass and hard food materials against the hard palate and crush teeth (Haggag et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A histological investigation was performed using a previously described method [ 59 ]. Colon fragments were collected and fixed in 10% formalin for 3 days, then dehydrated with ethyl alcohol in increasing concentrations (70°, 96° and absolute alcohol), clarified with 1-butanol and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%